Civil effects of canonical marriage contracted by Polish citizens before a clergyman of Roman Catholic Church abroad - TOMKIEWICZ, MAŁGORZATA (Prawo Kanoniczne, 2012)
The subject matter of this publication is providing the answer to the question whether Polish citizens have abroad the ability to contract marriage in canonical form (before a clergyman of Roman Catholic Church) which would be governed by Polish law. With regard to the complexity of problematic nature of the issue, the answer cannot be universal. It should be stated, however, that this kind of ability is not excluded by private international law rules, Polish law and canon law. A marriage of Polish citizens contracted in a country in which contracting marriage in canonical form is legally permitted, before a clergyman of Roman Catholic Church incardinated within territory of that country, will take effect in Polish law providing that all formalities required in the place of contraction are retained. This ability eventuates either from the lex loci celebrationis rule applied in private international law or bilateral agreements binding on Poland. There are also no such norms in rules at issue that would exclude the ability to contract marriage by Polish citizens abroad before a clergyman incardinated inPoland. A marriage contracted in such manner can be thereby recognized as marriage satisfying requirements from Article 1(2) and 1(3) of Family and Guardianship Code; and by this means as marriage contracted in the form of national law, as set out in Article 15(2) of private international law. Completion of registration requirements for the so-called marriage in a Polish registry office and drawing up marriage certificate involve certain difficulties of organizational and technical nature. It is not, nevertheless, infeasible. Within this situational scheme, the ability to contract marriage that would have legal force in Polish law does not exist solely on territory of countries in which acceptability of ancillary application of national law form has been excluded in bilateral agreements. Conversely, in all places where the said bilateral agreements are not applicable or do not include the mentioned limitations, contracting marriage in the canonical form before a Polish clergyman is subject to Polish law and is permissible even if the domestic law regulations provide only for the civil form.